Pelatihan Penyusunan Modul Ajar Kurikulum Merdeka Belajar Bagi Guru SD Negeri 13 Rantau Alai Kabupaten Ogan Ilir - Firmansyah; Annisa Astrid; Irja Putra Pratama; Zulkipli; Ferianto; Erisa Ardika Prasada (IAI Darussalam, 2024)
This community service activity aims to help partners, namely teachers of SD Negeri 13 Rantau Alai, Ogan Ilir Regency, to increase their understanding and skills in preparing teaching modules for the Merdeka Belajar Curriculum. The service implementation method used is in the form of educational training which was held on February 6-18, 2023 through four stages, namely: planning, implementation, evaluation, and reporting. This activity has been successfully carried out in accordance with the predetermined achievement targets. Based on the results of the measurements that have been taken, it is known that the average prestest score is 76 and the average post-test score is 92. The results of the pretest and post-test, as well as the practical performance of the training participants, showed significant results in increasing participants' understanding and skills in preparing the Merdeka Belajar Curriculum teaching module. The evaluation of the activity shows that the success of this activity is supported by the maximum contribution of the partners in providing facilities during the event and the enthusiasm of the participants in participating in the training. However, there are several obstacles such as time constraints and remote partner locations in areas with poor internet signals.